The bird of time: cognition and the avian biological clock - Cassone, Vincent M.; Westneat, David F. (Frontiers in Molecular Neuroscience, 2012)
Avian behavior and physiology are embedded in time at many levels of biological organization. Biological clock function in birds is critical for sleep/wake cycles, but may also regulate the acquisition of place memory, learning of song from tutors, social integration and time-compensated navigation. This relationship has two major implications. First, mechanisms of the circadian clock should be linked in some way to the mechanisms of all these behaviors. How is not yet clear, and evidence that the central clock has effects is piecemeal. Second, selection acting on characters that are linked to the circadian clock should influence aspects of the clock mechanism itself. Little evidence exists for this in birds, but there have been few attempts to assess this idea. At its core, the avian circadian clock is a multi-oscillator system comprising the pineal gland, the retinae and the avian homologues of the suprachiasmatic nuclei, whose mutual interactions ensure coordinated physiological functions, which are in turn synchronized to ambient light cycles via encephalic, pineal and retinal photoreceptors. At the molecular level, avian biological clocks comprise a genetic network of “positive elements” clock and bmal1 whose interactions with the “negative elements” period2, period3 and the cryptochromes form an oscillatory feedback loop that circumnavigates the 24 hrs of the day. We assess the possibilities for dual integration of the clock with time-dependent cognitive processes. Closer examination of the molecular, physiological, and behavioral elements of the circadian system would place birds at a very interesting fulcrum in the neurobiology of time in learning, memory and navigation.